THE INTERRELATIONSHIP BETWEEN CLINICAL AND ANATOMICAL TERMINOLOGY: A SCIENTIFIC ANALYSIS BASED ON MEDICAL LINGUISTICS, SEMANTIC STRUCTURE AND THE INTEGRATION OF CLINICAL THINKING (International journal of artificial intelligence, 2026)
This scientific article provides a comprehensive analysis of the interrelationship between clinical and anatomical terminology systems, their formation patterns, linguistic and semantic characteristics, and their role in modern medicine. Anatomical terminology is interpreted as a strictly standardized and semantically stable system that represents the normal structure of the human body. Clinical terminology, in contrast, is studied as a dynamic, multi-component, and semantically complex system that expresses diseases, pathological processes, diagnostics, and treatment strategies. The article highlights the morphological structure of terms, their semantic differentiation, functional load, and role in clinical thinking through an original scientific approach. It also substantiates the importance of the international standardization of terminology, its role in digital medicine systems, and global scientific communication.